Computational and experimental evidence of through-space NMR spectroscopic J coupling of hydrogen atoms - Dračínský, Martin; Jansa, Petr; Bouř, Petr (Chemistry (Weinheim an der Bergstrasse, Germany), 2012)
J coupling in NMR spectroscopy is conventionally associated with covalent bonds. A noncovalent contribution often called through-space coupling (TSC) has been observed for heavy atoms. In this study, the TSC was detected and analyzed for the more common (1)H-(1)H coupling as well. In synthesized model molecules the hydrogen positions could be well controlled. For several coupling constants the through-space mechanism was even found to be the predominant factor. The nature and magnitude of the phenomenon were also analyzed by density functional computations. Calculated carbon- and hydrogen-coupling maps and perturbed electronic densities suggest that the aromatic system strongly participates in the noncovalent contribution. Unlike covalent coupling, which is usually governed by the Fermi contact, TSC is dominated by the diamagnetic term comprising interactions of nuclei with the electron orbital angular momentum. The computations further revealed a strong distance and conformational dependence of TSC. This suggests that the through-space coupling can be explored in molecular structural studies in the same way as the covalent one.